KOMUNIKASI KELUARGA UNTUK MENGATASI KONFLIK INTERPERSONAL ANTARA REMAJA DAN ORANG TUA SAMBUNG - Shinta Maheswari, Irene; Naryoso, Agus; Qurrota Ayun, Primada (Interaksi Online, 2024)
Divorce and remarriage within a family often lead to interpersonal conflicts because the adjustment process for a teenager is not easy, especially when they have to communicate with stepparents. A teenager must adapt to life with a new family. This study aims to understand how family communication can resolve interpersonal conflicts and the strategies for resolving them between teenagers and stepparents. The theories used in this research are Family Relationship Schema Theory, Relationship Maintenance Theory, and Interpersonal Conflict Management Theory. This study uses an interpretive paradigm with a phenomenological approach and in-depth interview data collection techniques conducted with six individuals from three sets of teenage families and their stepparents. The results of this study indicate the importance of establishing dialogue between teenagers and stepparents to build trust within a blended family. Trust is formed through repeated shared experiences, such as daily family activities. Additionally, financial dependence of a teenager is also a reason to build trust. The variation in relationship schemas and family types in blended families is caused by different experiences determined by the communication patterns within each family. Relationship maintenance strategies, including openness, understanding, and involvement of third parties, are important to prevent conflicts in blended families. Withdrawal and exit response strategies are often used in conflict resolution, although they can create new conflicts due to unresolved feelings. This study emphasizes the importance of communication patterns in the dynamics and relationships of blended families